A cooperação energética brasileira à luz dos atos internacionais: atores e parceiros (1990-2020) - Feitosa, Lucas Marques (2021)
This dissertation discusses the energy cooperation carried out by Brazil in the energy area between 1990 and 2020, with special attention to the international acts signed in that period. Taking into account that each government of that period has particularities in relation to the realization of foreign policy, this research is structured around two main axes: to assess which are the main characteristics of the international acts signed by Brazil that deal with energy; and understand how these numbers are in line with what is said about the foreign policy of each government. The methodology used involved the construction of an original database, as well as the application of descriptive statistics and content analysis techniques. regarding chronology, typology, places of signature, signatories and partners in carrying out the acts. Data were found regarding the chronology and typology of the acts, places of signature, signatories and partners in Brazil. The findings also indicate that in general the signing of international acts was a reflection of the way in which Brazilian governments conducted their foreign policies.